Finding peace in clinical settings: A narrative review of concept and practice. Issue 4 (6th December 2016) - Austin, Philip; MacLeod, Roderick
ABSTRACT: The purpose of this review was to investigate and review the concept of "peace" and the role it plays in the spiritual well-being and care of people with a chronic or terminal illness. Our objectives were, first, to examine the importance of peace in palliative care as a measure of acceptance and in chronic illness settings as a predictor of improved survival. Second, we explored the dimensions of peace and their relationships with spiritual well-being. We further examined how the constructs of peace are assessed both within valid spiritual well-being measures and as individual items related solely to peace. Finally, we examined therapies aimed at promoting peace and emotional well-being in palliative and chronic illness settings. Despite much being written about different constructs of peace and the positive effects of being at peace during times of illness, the effects of therapies on the feeling of peace are not well-studied.